Cosmopolitanism and Communitarianism – How Globalization Is Reshaping Politics in the Twenty-First Century - Ruud Koopmans; Michael Zürn (The Struggle Over Borders. Cosmopolitanism and Communitarianism, 2019)
This chapter presents the theoretical framework and research design of the book. Drawing on cleavage theory, we argue that the new fault lines around globalization can no longer be captured along the classic redistributional left-right axis. From debates in political philosophy, we infer a distinction between `cosmopolitans', who advocate open borders, universal norms, and supranational authority, and `communitarians', who defend border closure, cultural particularism and national sovereignty. We also distinguish two hybrid positions, which we label `liberal nationalism' and `regionalism'. In terms of processes of social structuration underlying conflicts related to globalization, we distinguish three explanations: an economic one, centred around the differential materials costs and benefits for various collective actors; a cultural one, centred around access to transnational cultural capital and a political one that captures the differing degree to which actors have access to supranational forums of decision-making. Finally, we introduce the book's research design, the rationale behind the choice of countries and issues, and the main methods used to investigate them.
Keywords: 300; cosmopolitanism; communitarianism; globalization; political conflict; cleavage theory; populism; political ideology; political philosophy; social structuration; social class; research design